Business Ethics Disclosure - Ruminto, Azhar Wahid; Tiarani, Tiarani; jubaedah, siti (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This study aims to analyse the effect of board independence, gender diversity, managerial ownership, foreign ownership, and ownership concentration on business ethics disclosure. Design/methodology/approach: This research is a causality study with quantitative methods and uses secondary data sourced from annual reports and sustainability reports of manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2022. The sampling technique using purposive sampling obtained a sample of 75 sustainability reports which were analyzed using multiple linear regression.Findings: The research findings show that there is an effect of board independence, managerial ownership, and foreign ownership on business ethics disclosure but not significant for gender diversity and ownership concentration. Practical implications: This research contributes theoretically in the development of the accounting conceptual framework regarding the concept of disclosure, especially voluntary disclosure and contributes practically as a consideration for the government to make regulations that can encourage companies to disclose business ethics, can provide information to investors regarding business ethics disclosure items that can be used as material for evaluating long-term risks and opportunities related to their investment and as a consideration for decision making, policy or company strategy in disclosing business ethics. Paper type: Research paper